Description of a new species of the costata-group (Cladocera, Chydoridae, Aloninae) from Brazil - Sousa, Francisco Diogo R.; Santos, Sandro; Güntzel, Adriana Maria; Diniz, Leidiane Pereira; Júnior, Mauro De Melo; Elmoor-Loureiro, Lourdes M. A. (Zootaxa, 2015)
The aim of this study is to describe a new species of the costata-group from Brazil. Alona margipluma sp. nov. shares morphological traits with A. costata Sars, 1862, A. natalensis Sinev, 2008, and A. cheni Sinev, 1999, but differs from them in: (i) thin setulae between the marginal setae on the valves, (ii) setae 4–5 on the exopodite of limb III long and different in length, (iii) bottle-shaped sensillum on the basal endite of limb IV. For identification of Alona margipluma sp. nov. it is necessary to check carefully the main head pores and postabdomen characters since the former superficially resemble A. iheringula, A. setigera and Alona guttata.